The Effect of Fiscal Policy in Stabilizing Poverty - Bianka, Astina; Anggita Muslihani; Ayu Andira (UMBanjarmasin, 2023)
This research is motivated by fiscal policy which is a policy that has been carried out by the government in order to stabilize the economy in a country through existing expenditure and income from the government in the divisions of the budget in a country. The problem that occurs in this study is poverty that occurs in society which has many dimensions because it is related to inability in an economic field. Poverty has long been an economic problem among the people. The purpose of this study is also a forum to find out how the relationship between the influence of fiscal policy and stabilizing poverty that occurs. Then, the method used in writing this journal is a qualitative method where the results are data collection that is narrative in nature like journals in general. As a result, the government will set policies to expand economic development and reduce poverty. The government will also have the problem of increasing the deficit which has the potential and has determined the priority scale. So, the conclusion is that fiscal policy including tax and zakat management has a very significant impact in stabilizing poverty that occurs in a country. Taxes can be used to reduce the income gap and within a group of people. While zakat is also one of the existing fiscal policies in Islam and can reduce the stability of poverty. Then, in this global context, there is international cooperation with comprehensive fiscal policy managers that can help and reduce disparities in rich or poor countries